2014
DOI: 10.1149/04801.0081ecst
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Study on the Effects of Gas Channel Wettability in PEM Fuel Cells

Abstract: A numerical study on the effects of gas channel wettability in PEM fuel cells his item ws sumitted to voughorough niversity9s snstitutionl epository y theGn uthorF Citation: everwexsD wFD grixD F nd sferswD FD PHIPF e numeril study on the effets of gs hnnel wettility in iw fuel ellsF snX ondr¡ kD tFD xov¡ kD F nd f § D F @edsFAF roeedings of PHIP IQth snterntionl gonferene on edvned ftteriesD eumultors nd puel gells @efep IQAD frnoD gzeh epuliD PTEQH eugustF Additional Information:• he iletrohemil oietyD snF P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The volume of fluid (VOF) method along with a piecewise linear interface calculation is used for surface‐tracking in a fixed Eulerian mesh. In the current work, ANSYS FLUENT 17.2 software was used to numerically simulate unsteady laminar 2‐fluid model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The volume of fluid (VOF) method along with a piecewise linear interface calculation is used for surface‐tracking in a fixed Eulerian mesh. In the current work, ANSYS FLUENT 17.2 software was used to numerically simulate unsteady laminar 2‐fluid model.…”
Section: Methodsmentioning
confidence: 99%
“…The factors that affect the removing process include the gas flow velocity, the shape of the channel cross section and its dimensions, the droplet size, contact angle, and its emergence location. Alrahmani et al investigated numerically the effect of gas channel geometry on the water removal process in PEMFCs. Different configurations of gas channel cross section including square, trapezoid, semicircle, and triangle were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The design of traditional flow channels has received significant attention in the literature, with many numerical and experimental studies focusing on flow channel layout [2], shape [3] and wall hydrophobicity [4]. Numerical modelling shows that to minimise excess water saturation, a hydrophobic GDL should be combined with a hydrophilic straight flow channel to transport water from the GDL to the flow channel where it can be more easily removed [5,6]. However, at the bends in serpentine flow channels Song et al [4] demonstrated that a hydrophobic channel wall is best for minimising liquid saturation of the GDL.…”
Section: Introductionmentioning
confidence: 99%